Entrepreneurial Behaviour of Anthurium Growers in Aizawl District of Mizoram State (Indian Journal of Extension Education, 2018)
The study was conducted with 120 anthurium growers in Aizawl district of Mizoram state. The study revealed that majority of the anthurium growers under the study were of middle age, mostly got middle school, high school and higher secondary school level of education, most of the farmers possess medium size of landholding and medium size of land area under poly-house. Majority of them had medium level of annual income, medium marketing behaviour, medium extension contact and medium mass media exposure. Majority of the respondents had medium level of entrepreneurial behaviour followed by high and low level of entrepreneurial behaviour.